(untitled) (Journal of Hama University, 2024)
The aim of the research: the ieffect of using the flipped teaching strategy in teaching on developing of learning achievement to fifth grade students at the subject of science in Latakia city. The researcher choosed one unit from the biology studies book of the 5th grade students, then she designed this unit to be suitable for the exchanged strategy in teaching, s. Also, she made an achievement test to measure the achievement of the student in the subject of science> After that the researcher choosed a sample of fifth grade students in lattakia city, then she divided the sample into two groups (experiment group- control group), the researcher making sure of the equivalence between the two groups within the pre-applicate of the achievement test , then she taught the chosen unit to the (experiment group) by using the exchanged teaching strategy, and taught the same unit to the control group by using the usual way, then the researcher applied the achievement-test a in dimensional test. The researcher compare between the two groups and the results was: -there is a statistical significant difference in the means scores between the students of the two groups (experimental- control) in dimensional-test to the scale of beyond knowledge skills and this difference in favor of the experimental group, while the other group (control group) achieved. In the light of the results, the researcher presented some suggestion and of which the most important suggestion are: training the teachers to use the flipped learning in developing thinking skills and in educational attainment in biology studies.